[PP.22.25] SODIUM OVERLOAD AFFECTS THE SYMPATHOVAGAL BALANCE AND INDUCES MORPHOLOGICAL AND FUNCTIONAL CHANGES IN RAT AORTA. (September 2017) - Silva, J.C.S.; Peron, N.N.; Silva, M.B.; Silvestre, G.C.R.; Silva, A.Q.; Belo, V.A.; Castro, M.M.; Mostarda, C.; Silva, E.S.; Irigoyen, M.C.; Lacchini, S.
Abstract : Objective: To test the hypothesis that sodium overload induces vascular remodeling even in the absence of hypertension and that the autonomic nervous system may be mediating such modifications. Design and method: Male Wistar rats were divided in three groups: receiving tap water during 12 weeks (Cont, n = 9), NaCl 1% to drink for the last 2 weeks of treatment (Salt-2, n = 10), and NaCl 1% to drink for 12 weeks (Salt-12, n = 10). Blood pressure (BP) and heart rate (HR) were directly measured for BP and HR variabilities were calculated. Biomechanical properties of aorta were compared to histology and collagenase activity by zymography. Results: BP didn't change in Salt-12, but systolic BP slightly increased in Salt-2. BP variability and HR variability only increased after 12 weeks of saline overload (+28% SD-SBP and –45% VarRR interval). However, sympathetic modulation is already increased in Salt-2 and this increase is even greater in Salt-12 (+36% and +89%). Likewise, the parasympathetic modulation already reduces in Salt-2 and reduces further in Salt-12 (−7% and −19%), resulting in an increased autonomic modulation (LF/HF ratio: +51% and +140%). The aortic wall area increased in Salt-2 and Salt-12 groups (+25% and +16%). However, salt-2 reduced the adventitia/media ratio −26%), which may be related to the increase in MMP2 activity (+19%) and should have determined the reduction of the strainght (−23%N) and stress (−28% N/cm), as well as the increase of vessel deformation (+35% mm). On the other hand, Salt-12 rats increased the number of elastic lamellae (+25%), without significant alteration of MMP2 activity. This structural change may explain why the biomechanical evaluation was similar to the controls. However, Salt-12 aortas reduced the failure stress (−26%N/cm 2 ). Another important finding was the change in the type of collagen fibers deposited in the adventitia. Both Salt-2 and Salt-12 increased mature fibers and reduced immature fibers deposition. Conclusions: These results suggest that saline overload changes the sympatho-vagal balance and consequently interferes with the aortic structure, modifying its composition and functioning. The absence of hypertension together with increased autonomic modulation and vascular wall indicate that saline overload may lead to a pre-hypertensive condition.